A comprehensive analysis of biphasic reaction system for economical biodiesel production process. (March 2023) - Kim, Kyeongsu; Suh, Young-Woong; Ha, Jeong-Myeong; An, Jinjoo; Lee, Ung
Abstract: Biofuels are promising sources of renewable energy, however the economically feasible biofuel process has not yet proposed because of the system complexity and a wide range of process variations. This study explores the practical potential of biodiesel production processes through sequential reactions. Proposed sequential reaction started with xylose dehydration reaction producing furfural followed by furfural hydrogenation, condensation, and hydrodeoxygenation for biodiesel production. Rigorous reaction and separation models were constructed by using reaction experiments and thermodynamic data. The optimal biofuel process has been also proposed through flowsheet optimization. Detail technoeconomic analysis and life cycle assessment are provided to assess the impacts of certain parameters on economics and greenhouse gas emission. The results of this study show that the levelized cost of biodiesel production is 3.66 gal −1, and the corresponding global warming potential (GWP) is 57.18 gCO2eq MJ −1 for the base case. The production cost and GWP can reach 3.26 gal −1 and 29.39 gCO2eq MJ −1 depending on the xylose concentration and the furfural yield. The feed costs of xylose and hydrogen account for more than 80% of the levelized cost of biodiesel production and the steam utility required for refining products takes the largest portion of GWP, ranging from 33% to 65% of the total. These results ascertain that the economic feasibility of biodiesel production can be achievable by using only the sugar components in biomass, and the economics and GWP depend on the feed condition and the use of efficient separation process. © 2022 Elsevier Science. All rights reserved. Graphical abstract: Image 1 Highlights: Generic process design for biofuel production via biphasic reaction is suggested. Process model is constructed using experimental and thermodynamic data. Thermodynamic properties of biphasic solution highly affect process efficiency. Levelized cost of biodiesel is calculated as 3.26 gal −1 depending on feed condition. Climate change impact of the optimal process can be 29.39 gCO2 eq MJ −1 in optimistic case.